Partial volume correction for quantitative CEST imaging of acute ischemic stroke - Msayib, Y.; Harston, G. W. J.; Sheerin, F.; Blockley, N. P.; Okell, T. W.; Jezzard, P.; Kennedy, J.; Chappell, M. A. (Magnetic resonance in medicine, 2019)
Purpose Contributions of cerebrospinal fluid (CSF) have not been previously taken into account in the quantification of APT CEST effects, and correction for the dilution of CEST effects by CSF may allow for more robust measurement of CEST signals. The objective of this study was to compare the robustness of a partial volume (PV) correction model against a standard (4‐pool) multi‐pool model as far as their ability to quantify CEST effects in healthy, normal, and pathological tissue. Methods MRI data from 12 patients presenting with ischemic stroke, and 6 healthy subjects, were retrospectively analyzed. CEST signals derived from a 4‐pool model and a PV correction model were compared for repeatability and pathological tissue contrast. The effect of PV correction (PVC) was assessed within 3 ranges of tissue PV estimate (PVE): high PVE voxels, low PVE voxels, and the whole slice. Results In voxels with a high tissue PVE, PV correction did not make a significant difference to absolute APTR*. In low PVE voxels, the PVC model exhibited a significantly decreased ischemic core signal. The PVC measures exhibited higher repeatability between healthy subjects (4 pools: 3.4%, PVC: 2.4%) while maintaining a similar ischemic core CNR (0.7) to the 4‐pool model. In whole slice analysis it was found that both models exhibited similar results. Conclusions PV correction yielded a measure of APT effects that was more repeatable than standard 4‐pool analysis while achieving a similar CNR in pathological tissue, suggesting that PV‐corrected analysis was more robust at low values of tissue PVE.